2021
DOI: 10.1001/jamaneurol.2021.1008
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Persistent Disability in Patients With Pediatric-Onset Multiple Sclerosis

Abstract: for the Italian MS registry IMPORTANCE Availability of new disease-modifying therapies (DMTs) and changes of therapeutic paradigms have led to a general improvement of multiple sclerosis (MS) prognosis in adults. It is still unclear whether this improvement also involves patients with pediatric-onset MS (POMS), whose early management is more challenging. OBJECTIVE To evaluate changes in the prognosis of POMS over time in association with changes in therapeutic and managing standards. DESIGN, SETTING, AND PARTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 68 publications
4
28
0
Order By: Relevance
“…Over the last several years, multiple large observational studies have reported on long-term outcomes in patients with POMS [ 7 , 25 ]. A recent Italian registry study included a total of 3198 patients with POMS who were followed for an average of 21.8 years [ 7 ].…”
Section: Disability Outcomes Predictors and Importance Of Treatment In Pomsmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the last several years, multiple large observational studies have reported on long-term outcomes in patients with POMS [ 7 , 25 ]. A recent Italian registry study included a total of 3198 patients with POMS who were followed for an average of 21.8 years [ 7 ].…”
Section: Disability Outcomes Predictors and Importance Of Treatment In Pomsmentioning
confidence: 99%
“…Over the last several years, multiple large observational studies have reported on long-term outcomes in patients with POMS [ 7 , 25 ]. A recent Italian registry study included a total of 3198 patients with POMS who were followed for an average of 21.8 years [ 7 ]. The time to reach different disability levels was significantly decreased with each diagnosis epoch (up to 50–70% when compared with the natural history), which can be attributed mainly to the initiation of highly efficacious drugs during the pediatric age and continued use of DMT for a longer period of time when compared with prior epochs [ 7 ].…”
Section: Disability Outcomes Predictors and Importance Of Treatment In Pomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, we stratified this subgroup into 4 consecutive epochs of diagnosis, as defined by Baroncini and colleagues: before 1993, from 1993 to 1999, from 2000 to 2006, and from 2007 to 2013 (corresponding to the time of approval of pivotal DMTs in Italy). 26 Then, we reran the analysis as described above.…”
Section: Discussionmentioning
confidence: 99%